Analisis Pendidikan Formal Anak pada Keluarga Nelayan di Desa Karang Jaladri, Kecamatan Parigi, Kabupaten Ciamis, Provinsi Jawa Barat - Nani Suryani; Siti Aminah; Yastri Indah Kusumastuti (Buletin Ekonomi Perikanan, 2004)
Human resources development is a key to achieve a better quality of human life. One way to promote human quality of life is through involving people in education, both formal and informal education. The research focuses on how the fishermen family can takes advantages from formal education. It is expected, that the fishermen have good preferency to involve their chilbren to take formal education in order to broaden their mind and knowledge. From the research, it has been the shown that the distance of the school and the parents age, two factors affecting the willingness of the fishermen to send their children to scholl.